1995
DOI: 10.1515/bchm3.1995.376.8.495
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Activity of the Ternary Gelatinase B / TIMP-1 / LMW-Stromelysin-1 Complex

Abstract: Incubation of progelatinase B, isolated from human polymorphonuclear leukocytes, with TIMP-1 leads to the formation of the progelatinase B/TIMP-1 complex. This complex behaves like a Janus in a similar manner as we previously described for the progelatinase A/TIMP-2 complex. It shows the properties of TIMP-1 and is a better inhibitor for gelatinase A than for gelatinase B. Treatment with trypsin leads to activation of the binary complex. The activity, however, amounts only to slightly more than 10% of the acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 16 publications
1
20
1
Order By: Relevance
“…This is consistent with the theory that a ternary complex between MT1 MMP, TIMP2, and progelatinase A can form on the cell surface (17,18,37). In agreement with this, an E375A-progelatinase A⅐TIMP2 complex was able to inhibit MT1 MMP cat in a fluorimetric assay, 5 presumably due to the formation of a ternary complex as described by Kolkenbrock and colleagues (37)(38)(39).…”
Section: Discussionsupporting
confidence: 89%
“…This is consistent with the theory that a ternary complex between MT1 MMP, TIMP2, and progelatinase A can form on the cell surface (17,18,37). In agreement with this, an E375A-progelatinase A⅐TIMP2 complex was able to inhibit MT1 MMP cat in a fluorimetric assay, 5 presumably due to the formation of a ternary complex as described by Kolkenbrock and colleagues (37)(38)(39).…”
Section: Discussionsupporting
confidence: 89%
“…We have also shown that soluble aggrecanase in conditioned medium does not occur in a latent form that is activatable by exposure to APMA or trypsin. Indeed, aggrecanase activity appears to be destroyed by APMA exposure similar to that described for membrane type 2 MMP but not other members of the MMP family (23). This study has not addressed the potential of other physiological mechanisms for aggrecanase activation e.g.…”
Section: Discussionmentioning
confidence: 85%
“…This hypothesis is central to our current understanding of physiological activation of MMP-2 where the proMMP-2͞TIMP-2 complex is believed to inhibit MT-MMP and localize MMP-2 to the cell membrane where it is activated by membrane proteinases. However, in the case of the analogous proMMP-9͞TIMP-1 complex such involvement in cell surface activation has not been found, but proMMP-9͞TIMP-1͞Stromelysin-1 soluble ternary complex has been observed in vitro (44), proving that the inhibitory N terminus of TIMP-1 is functional in the complex. A major unsolved question in this context is how activated MMP-2 is released from the ternary complex.…”
Section: Resultsmentioning
confidence: 94%